Pengembangan Sistem E-Learning Bahasa Jepang Berbasis Adaptive Learning dengan Dukungan Artificial Intelligence - Rifky Akbar Vetian; Anis Lelitasari; Jihan Salsa Biela Fatin; Dina Dwi Astartia (Jurnal Riset Multidisiplin Edukasi, 2025)
Advances in information technology have enabled the creation of more effective and personalized learning systems. This research aims to design and implement an adaptive e-learning system for Japanese language learning supported by Artificial Intelligence (AI). This system adjusts the material, difficulty level, and delivery method according to the user's abilities and learning progress. The AI techniques used include machine learning to analyze student performance, natural language processing (NLP) to transmit Japanese text and conversations, and a recommendation system to provide appropriate materials. The research results are expected to improve the effectiveness of Japanese language learning for beginners to intermediate levels.